Abuse of Authority by the Directorate General of Taxes: State Administrative Law Perspective - Fransisca, Ika; Budianto, Arief Satrya; Widjiastuti, Agustin; Tedjokusumo, Dave David (DE'RECHTSSTAAT, 2025)
Abuse of authority by state officials, including Directorate General of Taxation (DGT) may potentially occur, either in the form of intentional abuse of authority or errors in the use of authority. With the authority granted by legislation, DGT performs supervisory functions that grant it the authority to conduct tax audits, expand the taxpayer base (WP), and intensify tax collection through clarification letters (SP2DK). This study analyses the forms of abuse of authority by DGT, both those involving intentional misuse of power (abuse of power) and errors in the use of authority without malicious intent and without deviating from the original purpose (misuse of authority). In the execution of its supervisory functions, DGT may commit either of these errors due to the oversight procedures that do not adequately balance the rights and obligations between DGT and taxpayers, weak oversight, and the asymmetry of tax regulation knowledge between DGT and taxpayers. This study also discusses the solutions that administrative law can offer to eliminate the abuse of authority, including implementing cooperative compliance and external supervision.